Forests and the Kyoto protocol: implications for Asia's forestry agenda - Smith, J. (Island Press, 2002)
Economists have long argued that payment for the environmental services of forests could contribute to forest conservation and sustainable use. The Clean Development Mechanism (CDM) of the Kyoto Protocol could make this concept a reality by allowing carbon-emitting industries in developed countries to meet a part of their emission reduction commitments by financing forestry projects that sequester carbon or protect carbon stocks in developing countries. The author argues that the CDM should not be seen as yet another silver bullet for saving tropical forests. However, there are ways to implement the CDM that could enhance the effectiveness of more conventional approaches and leverage support from stakeholders with conservation and development agendas. Implementing the CDM purely as a tool for carbon farming could derail the new forestry agenda. Proactive efforts will be needed in crafting CDM rules and designing projects such as embed CDM projects in an integrated program for sustainable forest management, prevent perverse incentives, use the CDM to leverage financial support for other environmental services and livelihood benefits. (YS)